PERANCANGAN SISTEM INFORMASI JADWAL KEBERANGKATAN DAN KEDATANGAN BUS DITERMINAL SRITANJUNG KABUPATEN BANYUWANGI - Zahrafil Jannah; Zaehol Fatah; Anwar Anas (Jurnal Riset Teknik Komputer, 2025)
Currently, technological developments are rapid and dynamic. The manual systems currently in use are deemed inadequate to handle the workload, particularly for routine terminal activities such as recording bus data, monitoring departure schedules, and monitoring arrivals. This situation has prompted the need for a computerized system. Sritanjung Terminal, as one of the main terminals in Banyuwangi Regency, plays a crucial role not only as a transportation service center but also as a source of information for the public. However, the terminal still relies on manual methods, using ledgers, to run its operations. This conventional approach presents numerous challenges, necessitating a shift to a more modern system, namely automated computer-based data management.To address these challenges, this research was conducted through several stages, including field observation, interviews, documentation collection, system design, programming, testing, and system implementation. The final result of this research is the creation of an application capable of managing bus departure and arrival schedules at Sritanjung Terminal in a structured manner according to a predetermined flow. With this application, it is hoped that various operational issues that have arisen can be resolved more effectively and efficiently.